Analysis of mathematical literacy based on mathematical resilience of fifth grade elementary school students - Fembriani; Yusuf , Munawir; Subagya (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This study aims to describe the literacy of students in solving mathematical literacy problems based on the level of mathematical resilience. This study used a case study qualitative research method. The research subjects were 20 grade V elementary school students for the 2020/2021 academic year. Data collection techniques using questionnaires, tests, and interviews. Processing the validity of data using technical triangulation techniques. Data analysis techniques using miles and hurry (reducing data, presenting data, drawing conclusions). The results of study showed that students with different levels of mathematical resilience have different mathematical literacy abilities. Students with high mathematical resilience have mathematical literacy skills, which are aspects of formulate, employ and interpret. Students with medium resilience have mathematical literacy skills, which are aspect of formulating problems, while students with low mathematical resilience do not have the three abilities of mathematical literacy.